PROSPECTS AND CHALLENGES OF DIGITAL TECHNOLOGY BASED DANCE ASSESSMENT - Nursilah; Ayu, Anjani; Fajriani, Berliana (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
This article explores the dynamic prospects and challenges that arise in digital-based dance assessment. In an era where digital technology is increasingly integrated in various aspects of life, dance is undergoing a significant transformation, particularly in terms of assessment and evaluation. This research aims to identify and analyze how technologies such as artificial intelligence, sensorbased movement analysis, and virtual reality, can provide new methods of objective and detailed dance assessment. Through a qualitative approach involving interviews with dance professionals, analysis of relevant literature, and case studies, this article reveals how technology can support and enrich dance assessment practices. The results show that while digital-based technologies offer the possibility of more precise and in-depth assessment, aspects such as artistic interpretation and the uniqueness of dance expressions cannot always be effectively measured with digital methods. This article contributes to the discussion on the integration of technology in dance by highlighting the importance of finding a balance between the utilization of technology and the preservation of aesthetic and traditional values in dance. In conclusion, while digital technology has great potential in dance assessment, there needs to be awareness and strategies to overcome its limitations in order to maintain the integrity of dance.